Pengaruh Customer Engagement Terhadap Brand Loyalty Pada Pengguna Maxim Di Kota Padang - Nita Alida Sari Hasibuan; Rose Rahmidani (Universitas Negeri Padang, 2023)
The purpose of this study is to determine the impact of customer retention on the brand loyalty of Maxim users in the city of Padang. The type of research applied is causal research. The study population was Padang City residents who had used Maxim at least 2 times in the past month. In determining the sample size, the researchers used the Cochran formula, with a total sample size of 97. In this study using a targeted sampling technique, the data used were raw data types generated by distributing questionnaires to residents of Padang city according to predetermined criteria. Using path analysis of SPSS 22 as the analysis method, the results show that customer participation has a significant positive impact on brand loyalty